Application of Problem Based Learning Model to Enhance Learning Outcome on Q.S. Al-Hujurat Ayat 13 in Class IV - Gozali, Atep Rahmat; Salahudin, Anas (Al-Aulad: Journal of Islamic Primary Education, 2023)
This study aims to enhance learning outcomes in Class IV, particularly on the understanding of Q.S. Al-Hujurat Ayat 13, through the Problem-Based Learning (PBL) model in Islamic Religious Education. Classroom Action Research (CAR) method is utilized to address students' insufficient concentration and passivity during learning. Results reveal significant improvements in understanding, engagement, and motivation among students. Before the intervention, students struggled to grasp the material through traditional lecture and assignments. However, after implementing PBL, students demonstrated a notable increase in comprehension, learning outcomes, and motivation. In Cycle I, 60% of students showed improvement, rising to 93.33% in Cycle II, achieving satisfactory grades. The findings indicate that PBL effectively addresses learning difficulties, particularly in understanding Q.S. Al-Hujurat Ayat 13, emphasizing the importance of engaging learning methods and appealing instructional materials in Islamic education for Class IV students.